Morphological, biochemical and molecular characterization of potential plant growth-promoting rhizobacterial strains from metroxylon sagu Rottb. (Sago) palms. - Nemenzo, Phoebe S.
Three bacterial strains isolated from the rhizophere of metroxylon sagu Rottb. (sago) palms in Agusan Marsh, Mindanao were previosly observed to have potential plant-promoting properties, i.e, increasing tha radicle length in corn varietes, viz, NK 5447 Bt and NK 5447 conventional and increasing the shoot length in tomato varieties, viz, Improved Pope and Diamante.
Thesis, Masteral (MS in Microbiology)--UP Diliman
Keywords: Rhizosphere of metroxylon sagu Rottb